Analyzing Test Smells Refactoring from a Developers Perspective - Damasceno, Humberto; Bezerra, Carla; Coutinho, Emanuel; Machado, Ivan (Anais do Simpósio Brasileiro de Qualidade de Software (SBQS); 2022: Anais do XXI Simpósio Brasileiro de Qualidade de Software, 2022)
Test smells represent a set of poorly designed tests, which can harm a test code’s maintenance and quality criteria. Although fundamental steps to understand test smells have been investigated, there is still an evident lack of studies evaluating the impact of test smell refactoring from internal quality attributes, such as size, cohesion, coupling, and complexity. In addition, the literature still lacks research that addresses the difficulties developers encounter during test smell refactoring. The paper investigates the impact of test smell refactoring from developers’ perspectives and internal quality attributes. We investigated the perceptions and difficulties encountered by 20 developers while removing 5 types of test smells in 4 open-source projects over two months. Through this experiment, we analyzed: (i) the impact that test smell refactoring has on internal quality attributes; (ii) developers’ perception of test smells as actual problems within a software system; and (iii) main difficulties encountered by developers during test smell refactoring. Our findings can help developers design a prioritization scheme for test smell refactoring and make them aware of the real benefits of test smell refactoring.